A DESCRIPTIVE STUDY ON THE ABILITY IN UNDERSTANDING ENGLISH TEXT OF THE SECOND YEAR STUDENT OF SMU N 1 MANYARAN WONOGIRI - WAHYUNI , SITI (2007)
The research has two objectives; ( 1 ) to analyze the students ability in understanding English text by applying the four reading skills (skimming, scanning, reading for detail information and reference skill ) and ( 2 ) to identify the reading skills that the students get difficulties in practice. Considering these aims, the writer uses descriptive method. The population of the research was the second year students of SMU N 1 Manyaran, Wonogiri in 2007/2008 academic year. The writer used random sampling in choosing the sample. The writer took 44 students out of the 308 students. In collecting the data, the writer used tests. The result of the research shows that students make 1356 correct answers out of the 1848 answers. The percentage of the correct answers is 73.3 % out of 1356 correct answers, the distribution is 367 in skimming, 356 in scanning, 263 in reading for detailed information and 370 in reference skill. The percentage of those four reading skill are 69.5 %, 89.8 %, 59.7 % and 76.4 % respectively. The percentages show that skimming and reference skills belong to “good” category, scanning skill belongs to “very good” category, and reading for detailed information belongs to “fair” category. The conclusion that can be taken from the study is that the level of the student ability in understanding English text by applying the four reading skills is good. The most difficult reading skill for the students is reading for detailed information, while, the easiest reading skill is scanning.